Defeminization of practicing dentists: A national perspective - Masood Aslam, Sanaa; Ahsin, Emaan; Um Min Allah, Nasar (Journal of the Pakistan Medical Association, 2023)
Madam, The dental profession has witnessed a progressive shift where female dentists are becoming more prevalent in many countries, including Pakistan. This trend, known as the feminization of dentistry1, can be attributed to changing societal and economic perceptions, increased acceptance of diverse gender roles, and the recognition of the benefits of adopting feminine traits in the dental profession.2 In Pakistan, the transition began in the early 1990s when the quota system limiting seats for women in medical and dental schools was abolished. Currently, around 70% of undergraduate dental students in Pakistan are female.2 However, despite the promising number of female dental students, there is a significant drop in postgraduate training and professional practice. Only 5% of graduating female dentists pursue postgraduate training, and only half of the registered female dentists work.3 The reasons for this decline include a glass ceiling effect, which hinders women's advancement in their careers, the lack of female representation in leadership roles, the absence of female mentorship at the postgraduate level, and dual family and domestic responsibilities. Additionally, female dentists may face bias and preference towards their male counterparts in high-status specialities, impacting their promotional opportunities and patient preferences.4,5 Persistence of societal pressure and traditional gender roles also contribute to the dropout rate of female dentists in Pakistan. Many young women are often pressured to prioritize family obligations over professional commitments, leading them to leave the dental profession early. Moreover, the absence of part-time options further limits their ability to balance family responsibilities with dental practice. To address these challenges and enable the sustained involvement of female dentists, several measures are necessary. Increasing female representation in leadership roles, make leadership part of the educational curriculum, providing mentorship opportunities, and establishing strong social support systems for women are crucial. Reforms should also focus on improving ergonomics in dental practice, highlighting cultural loopholes for gender biases, equity issues and implementing policies that support working mothers, such as flexible working hours, adequate maternity leave and family care facilities. While efforts have been made to increase the number of female dental students, there is still a long way to go in creating an inclusive and supportive environment for practicing female dentists in Pakistan. By addressing the root causes of the gender disparity and implementing necessary reforms, Pakistani society can break the glass ceiling and allow future generations of women to contribute fully to the field of dental healthcare.